Pengembangan Modul Pembelajaran Ilmu Pengetahuan Sosial Berbasis Inkuiri - Thomas Wijaya; Nova Adi Kurniawan (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2021)
This article aimed to provide an overview of the development of inquiry-based Social Science learning modules with a material of business models in economic activities for the fifth grade of elementary school students. This study also aimed to increase students' learning activities through that module. The goal derived from the low level of students' learning activities and the less varied teaching materials used. The development model for this module followed Bord & Gall. The developed modules were researched and assessed by a team of experts, which consisted of Social Studies and Inquiry Learning experts (87.03%), Materials experts (90.89%), Language experts (87.5%), and Media experts (79.33 %). Overall, the assessment reached 86.18% which was categorized as very good. At the same time, students' responses to the developed modules have an overall percentage of 90.13% which was also very good. In addition, students' learning activities before and after using the module obtained t-count (18.272), while the t-table was 2.045. So, it indicated that t-count ≥ t-table, meaning that accepted Ha and rejected Ho. Therefore, students' learning activities have increased after using the developed inquiry-based social studies learning module.